Willingness to vaccinate against COVID-19 might be systematically underestimated - Marc Oliver Rieger (Wolters Kluwer Medknow Publications, 2021)
Estimations of the willingness to vaccinate against COVID-19 are important to plan the vaccination process and also to coordinate efforts to reach herd immunity.Aims and Objectives: In this article, we test standard measures of vaccination willingness against systematic biases caused by misunderstandings and lack of information. We use a survey among 730 persons living in Germany at the start of the official vaccination program. We elicit willingness to vaccinate first in a standard form, and then again after clarifications and after providing additional information. We find that a substantial number of persons who state initially that they do not want to get vaccinated does so simply because they want to let people with higher risk be vaccinated first. Appropriately rephrasing the question increases the willingness by around 5 percentage points. Information about herd immunity increases the willingness by additional 7%, confirming previous findings. Standard survey-based estimates of vaccination willingness might underestimate the real number of persons who want to get a vaccination. This number can be increased even further by simply providing appropriate information on herd immunity. In our sample this increased vaccination willingness from 71.4% to 83.6%.